Sperm Associated Antigens: Vigorous Influencers in Life - Samaneh Faraji (Royan Institute (ACECR), Tehran, 2021)
Sperm associated antigens (SPAGs) are specific proteins in terms of performance and evolution, that have common expressions in the testes or sperm cells. Moreover, the humoral immune response against some of SPAGs can result in immunological infertilities. On the other hand, recent studies have explored several new properties of SPAGs and shed light on sperm's function, the impact of anti-sperm antibodies (ASA) in immunological infertility, and some tumors related to SPAGs. This article presents an exhaustive review of SPAGs and their roles in the cell cycle, signaling pathways, fertility, sperm-oocyte cross-talk as well as their unfavorable positions as prognostic factors in many types of cancers.